Avaliação Normativa dos convênios federais firmados entre a SUDAM e os municípios do Estado do Pará, 2016-2019 - FALESE, Sérgio Guilherme dos Santos (Universidade Federal do Pará, 2023)
This dissertation aims to evaluate the agreements signed between SUDAM and the Municipalities of the State of Pará in relation to current legislation and the Regional Development Plan for the Amazon (PRDA). To support this work, a literature review was carried out, initially with an approach on local development, making a contextualization focused on the development of the Legal Amazon; then, the main concepts related to voluntary transfers are explained, with emphasis on one of its modalities - the agreements and, finally, the research carried out at SUDAM is presented, making a survey, in the period from 2016 to 2019, on the agreements finalized by SUDAM with Municipalities of Pará, in order to identify the main execution failures and if they have been coherent with the PRDA. At the end of the research, necessary recommendations are proposed in this regard and a Manual to serve as a guide in the celebration, execution and accountability of agreements with SUDAM.